A Study on the Change and Development Strategies of E-Commerce Industry in China - 김병구(Byoung-Goo KIM); 이천수(Chunsu LEE) (International journal of industrial distribution and business, 2024)
Purpose: The purpose of this study is to explore the development and characteristics of e-commerce in China and analyze the current status of e-commerce platforms in China. Research design, data and methodology: To explore the development of e- commerce in China, this study collects and analyzes Chinese journals and secondary sources. It also conducts a case analysis of the success strategies of leading Chinese e-commerce companies. Results: The analysis showed that China's e-commerce is active in various forms of e-commerce, including B2B, B2C, and C2C, and that the development of e-commerce in China has been divided into three main stages. The Chinese government has been actively implementing various policies to promote the development of e-commerce. Conclusions: In this context, this paper specifically examines the development process of e- commerce in China, the current status of the Chinese e-commerce market, and the characteristics of the Chinese e-commerce market. In addition, the paper analyzes representative B2B, B2C, and C2C companies in China's e-commerce market. The results of the analysis show that Huichongwang, a B2B company, Jingdong, a B2C company, and Taobao, a C2C company, have achieved rapid growth through their core strategies and capabilities. The study also analyzed in detail the problems faced by the Chinese government and companies.